A randomized, placebo-controlled trial of intradiscal electrothermal therapy for the treatment of discogenic low back pain - Pauza, Kevin J; Howell, Susan; Dreyfuss, Paul; Peloza, John H; Dawson, Kathryn; Bogduk, Nikolai (The spine journal, 2004)
Intradiscal electrothermal therapy (IDET) is a treatment for discogenic low back pain the efficacy of which has not been rigorously tested. To compare the efficacy of IDET with that of a placebo treatment. Randomized, placebo-controlled, prospective trial. Patients were recruited by referral and the media. No inducements were provided to any patient in order to have them participate. Of 1,360 individuals who were prepared to submit to randomization, 260 were found potentially eligible after clinical examination and 64 became eligible after discography. All had discogenic low back pain lasting longer than 6 months, with no comorbidity. Thirty-seven were allocated to IDET and 27 to sham treatment. Both groups were satisfactorily matched for demographic and clinical features. IDET was performed using a standard protocol, in which the posterior annulus of the painful disc was heated to 90 C. Sham therapy consisted of introducing a needle onto the disc and exposing the patient to the same visual and auditory environment as for a real procedure. Thirty-two (85%) of the patients randomized to the IDET group and 24 (89%) of those assigned to the sham group complied fully with the protocol of the study, and complete follow-up data are available for all of these patients. The principal outcome measures were pain and disability, assessed using a visual analog scale for pain, the Short Form (SF)-36, and the Oswestry disability scale. Patients in both groups exhibited improvements, but mean improvements in pain, disability and depression were significantly greater in the group treated with IDET. More patients deteriorated when subjected to sham treatment, whereas a greater proportion showed improvements in pain when treated with IDET. The number needed to treat, to achieve 75% relief of pain, was five. Whereas approximately 40% of the patients achieved greater than 50% relief of their pain, approximately 50% of the patients experienced no appreciable benefit. Nonspecific factors associated with the procedure account for a proportion of the apparent efficacy of IDET, but its efficacy cannot be attributed wholly to a placebo effect. The results of this trial cannot be generalized to patients who do not fit the strict inclusion criteria of this study, but IDET appears to provide worthwhile relief in a small proportion of strictly defined patients undergoing this treatment for intractable low back pain.